Adherence to a Gluten-Free Diet and Frequency of Inadvertent Consumption of Gluten-Containing Foods in Adult Patients With Celiac Disease in Ankara, Turkey - Aksan, Aysegul; Aksan, Sami; Stein, Jurgen; Mercanligil, Seyit Mehmet (Nature Publishing Group, 2017)
[Abstract Not Available]
82nd Annual Scientific Meeting of the American-College-of-Gastroenterology (ACG) -- OCT 13-18, 2017 -- Orlando, FL